Lipid-Reactive T Cells in Immunological Disorders of the Lung - Ryu, Seungwon; Park, Joon Seok; Kim, Hye Young; Kim, Ji Hyung (Frontiers in Immunology, 2018)
Regulation of T cell-mediated immunity in the lungs is critical for prevention of immune-related lung disorders and for host protection from pathogens. While the prevalent view of pulmonary T cell responses is based on peptide recognition by antigen receptors, called T cell receptors (TCR), on the T cell surface in the context of classical major histocompatibility complex (MHC) molecules, novel pathways involving the presentation of lipid antigens by cluster of differentiation 1 (CD1) molecules to lipid-reactive T cells are emerging as key players in pulmonary immune system. Whereas, genetic conservation of group II CD1 (CD1d) in mouse and human genomes facilitated numerous in vivo studies of CD1d-restricted invariant natural killer T (iNKT) cells in lung diseases, the recent development of human CD1-transgenic mice has made it possible to examine the physiological roles of group I CD1 (CD1a-c) molecules in lung immunity. Here, we discuss current understanding of the biology of CD1-reactive T cells with a specific focus on their roles in several pulmonary disorders.